Beach house memories [large type] - Monroe, Mary Alice (Thorndike Press large print core series., 2012)
"Olivia "Lovie" Rutledge lives in her beloved Primrose Cottage on Isle of Palms with her daughter Cara. Lovie remembers many summers, but especially 1974. Lovie had always done what was expected -- marrying Stratton Rutledge and turning over her fortune and fate to his control. But she refuses to relinquish her family's seaside cottage where she indulges her vocation as a "Turtle Lady", tending the loggerhead sea turtles. This summer, however, is different. Visiting biologist Russell Bennett arrives on the island to research loggerheads. What begins as a shared passion for turtles changes to a love far more passionate and profound than Lovie has ever known" -- Cover verso.